Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1159/000518370
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Incidence of Stroke in a General Population of 1.4 Million Japanese: The Shiga Stroke Registry

Abstract: <b><i>Introduction:</i></b> The purpose of this study was to investigate seasonal variation in stroke incidence using data from a large-scale stroke registry of general population in current Japan. <b><i>Methods:</i></b> Shiga Stroke Registry (SSR) is an ongoing population-based registry of stroke that occurred in the Shiga Prefecture in central Honshu, Japan. A total 6,688 cases of first-ever stroke, with onset dates ranging from 1 January 2011 to 31 December in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Various studies from different regions of the world support a winter peak in the incidence of stroke. [4][5][6][7][8][9][10][11][12] Seasonality in several cardiovascular risk factors may explain this winter peak, specifically in the elderly population. Fibrinogen, for instance, is an independent risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies from different regions of the world support a winter peak in the incidence of stroke. [4][5][6][7][8][9][10][11][12] Seasonality in several cardiovascular risk factors may explain this winter peak, specifically in the elderly population. Fibrinogen, for instance, is an independent risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…3 Seasonal variations in the incidence of stroke have been examined in numerous studies worldwide. Most studies reported a winter peak in the occurrence of stroke, [4][5][6][7][8][9][10][11][12] others found no seasonal variation [13][14][15] and fewer showed a summer peak 16 or an autumn peak. 17 Data on whether seasonality of stroke differs with age are limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seasonal uctuations have been documented for a variety of different diseases across a broad range of populations and climates. In particular cardiovascular [10,11] and cerebrovascular diseases [12,13] have shown a ´winter peak´ and through in summer. This has been attributed to changes in ambient temperature, as mentioned morbidities were negatively correlated to it.…”
Section: Discussionmentioning
confidence: 99%